Women’s devotions in the epigraphy of Roman Lusitania - Molina-Torres, Maria Pilar (Journal of the Belarusian State University. History, 2024)
The main motivation for this research is the lack of works on the history of Lusitanian women. Despite the numerous studies on the Roman religious world, there is a significant lack of research on the interpretation of women’s beliefs in Lusitania. From a gender perspective, this line of research has been particularly innovative in recent decades and has been taken up by various researchers who have updated the epigraphic corpora and subjected the subject to a profound process of debate and reflection. The epigraphic documentation provides a series of specific references to the geographical area in which the Lusitanian women’s cults were established. It is precisely through the votive inscriptions that we can see how the women of the southwest of the Iberian Peninsula, consciously or unconsciously, took advantage of the cultural change to take a more interested approach to their cultic demands, both in their religious and personal spheres. It should be added that the prototype of the devout Lusitanian woman is defined by her predilection for certain gods, protectors of her personal and family environment, which to some extent determined her choice of religious practices. Most of these ritual practices took place in sanctuaries or places of worship located in rural areas, with a clear diffusion and permanence of pre-Roman beliefs that coexisted with Roman cults. In fact, the lack of archaeological documentation is an obstacle to a more detailed knowledge of the religious epigraphy of a rural world, allowing to make a global analysis of its socio-cultural context.